(untitled) (Research, Society and Development, 2023)
Buccal fat pad excision, commonly known as bichectomy, is offered in facial harmonization as a means of achieving a more aesthetic middle third of the face. Such a procedure has gained popularity in offices in search of facial profiles with the most evident angularities and aesthetically within a harmonious and less rounded balance. It is worth emphasizing to the patient the need to clarify that often the procedure performed alone does not provide the idealized aesthetic gain. It is even more important to remember that this is a surgical procedure that involves noble surrounding areas and, therefore, has its risks and possible complications. Thus, the objective of this research is to narratively review the literature on bichectomy surgery for rejuvenation in orofacial harmonization.